# The Fibonacci sequence

From HaskellWiki

Implementing the Fibonacci sequence is considered the "Hello, world!" of Haskell programming. This page collects Haskell implementations of the sequence.

## Contents

## Naive definition

```
fib 0 = 0
fib 1 = 1
fib n = fib (n-1) + fib (n-2)
```

## Linear-time implementations

One can compute the first *n* Fibonacci numbers with *O(n)* additions.
If `fibs`

is the infinite list of Fibonacci numbers, one can define

```
fib n = fibs!!n
```

### Canonical zipWith implementation

```
fibs = 0 : 1 : zipWith (+) fibs (tail fibs)
```

### With scanl

```
fibs = fix ((0:) . scanl (+) 1)
```

### With unfoldr

```
fibs = unfoldr (\(f1,f2) -> Just (f1,(f2,f1+f2))) (0,1)
```

### With iterate

```
fibs = map fst $ iterate (\(f1,f2) -> (f2,f1+f2)) (0,1)
```

## Log-time implementations

### Using 2x2 matrices

The argument of `iterate`

above is a linear transformation,
so we can represent it as matrix and compute the *n*th power of this matrix with *O(log n)* multiplications and additions.
For example, using the simple matrix implementation in Prelude extensions,

```
fib n = head (apply (Matrix [[0,1], [1,1]] ^ n) [0,1])
```

This technique works for any linear recurrence.

### A fairly fast version, using some identities

```
fib 0 = 0
fib 1 = 1
fib n | even n = f1 * (f1 + 2 * f2)
| n `mod` 4 == 1 = (2 * f1 + f2) * (2 * f1 - f2) + 2
| otherwise = (2 * f1 + f2) * (2 * f1 - f2) - 2
where k = n `div` 2
f1 = fib k
f2 = fib (k-1)
```

### Another fast fib

```
fib = fst . fib2
-- | Return (fib n, fib (n + 1))
fib2 0 = (1, 1)
fib2 1 = (1, 2)
fib2 n
| even n = (a*a + b*b, c*c - a*a)
| otherwise = (c*c - a*a, b*b + c*c)
where (a,b) = fib2 (n `div` 2 - 1)
c = a + b
```

### Fastest Fib in the West

This was contributed by wli (It assumes that the sequence starts with 1.)

```
import Data.List
fib1 n = snd . foldl fib' (1, 0) . map (toEnum . fromIntegral) $ unfoldl divs n
where
unfoldl f x = case f x of
Nothing -> []
Just (u, v) -> unfoldl f v ++ [u]
divs 0 = Nothing
divs k = Just (uncurry (flip (,)) (k `divMod` 2))
fib' (f, g) p
| p = (f*(f+2*g), f^2 + g^2)
| otherwise = (f^2+g^2, g*(2*f-g))
```